Employees’ Participation in Management: International Experiences and the Prospects for Canada - Jecchinis, Chris (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The experiences of certain successful West European practices in employee's participation within undertaking recommend the establishment of complementary institutional arrangements in the existing system of labour-management relations in Canada which, at the present, is based only on the institution of collective bargaining.